Dual voices, hybrid identities: the recontextualization of research in digital dissemination scientific discourse - Lorés, Rosa (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The current demands placed on scientists to increase public awareness of their findings involves recontextualizing highly technical research to be understood by diversified audiences. In the present study, a corpus of 20 online digests drawn from the British Psychological Society website, which are condensed versions of recently published research articles, is quantitatively and qualitatively explored in terms of the (meta)discoursal features that the scriptwriter uses to foster comprehensibility, project a credible and authoritative voice and enhance engagement with their audience, as a way to bridge the existent knowledge asymmetries. The analysis revealed the existence of discoursal and pragmatic, as well as some multimodal, resources (i.e. code glosses, hyperlinking, evidentials, engagements markers) used by the scriptwriters to project a dual voice which aligns both with the expert and with the diversified audience, thus projecting a hybrid authorial identity.